2014
DOI: 10.1002/bies.201400118
|View full text |Cite
|
Sign up to set email alerts
|

Histone proteolysis: A proposal for categorization into ‘clipping’ and ‘degradation’

Abstract: We propose for the first time to divide histone proteolysis into “histone degradation” and the epigenetically connoted “histone clipping”. Our initial observation is that these two different classes are very hard to distinguish both experimentally and biologically, because they can both be mediated by the same enzymes. Since the first report decades ago, proteolysis has been found in a broad spectrum of eukaryotic organisms. However, the authors often not clearly distinguish or determine whether degradation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 138 publications
3
48
0
Order By: Relevance
“…This area of study is clearly poised for significant expansion, as evidenced by the identification of two H2A-specific proteases and several novel histone clipping events in just the past few years (39 -42). Discerning whether any histonecleaving event is the result of continuous histone turnover or sample degradation versus an alternative biological process with epigenetic implications is challenging (36). Our in vitro data suggest that cathepsin L might be a potential candidate to explain some of the truncated histone H2A proteoforms we observed in the butyrate-treated HeLa cell histone samples.…”
Section: Discussionmentioning
confidence: 89%
“…This area of study is clearly poised for significant expansion, as evidenced by the identification of two H2A-specific proteases and several novel histone clipping events in just the past few years (39 -42). Discerning whether any histonecleaving event is the result of continuous histone turnover or sample degradation versus an alternative biological process with epigenetic implications is challenging (36). Our in vitro data suggest that cathepsin L might be a potential candidate to explain some of the truncated histone H2A proteoforms we observed in the butyrate-treated HeLa cell histone samples.…”
Section: Discussionmentioning
confidence: 89%
“…Kouzarides and colleagues also reported that an endopeptidase in Saccharomyces cerevisiae cleaves the first 21 residues from H3 (47). A number of groups have reported different candidate enzymes responsible for the cleavage of histone tails (4,5). However, systematic characterization of the enzyme family(ies) responsible for this activity has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the biological significance of this modification is not well understood. It has been suggested that the proteolytic cleavage of histone tails plays critical roles in a variety of processes, including control of the cell cycle, development, response to infection, embryonic stem cell differentiation, aging, spermatogenesis, and sporulation (4,5). Due to the diversity of histone tail modifications, a critical question is whether a family of proteases specifically recognizes individual modified histone tails in different contexts, similar to other histonemodifying enzyme families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post translational modifications (PTMs) 1 of histones play a major role in regulation of chromatin functionality. Evidence is emerging that not only "classical" histone PTMs, such as methylation, acetylation, and phosphorylation at distinct residues, but also proteolytic processing of nucleosome proteins, known as "histone clipping," can be involved in regulation of key cellular processes, such as transcriptional regulation, cell differentiation, and senescence (1)(2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%